Seventh Day Syndrome Revisited: Early Recognition of the Clinical Syndrome and an Evolving Understanding of Its Etiology - Halle-Smith, James M.; Hall, Lewis A.; Hann, Angus; Hartog, Hermien; Perera, M. Thamara P. R.; Neil, Desley A. H. (Frontiers in Transplantation, 2022)
Background: Unexplained acute failure of an initially functioning liver graft early post-transplant has been described as Seventh-Day Syndrome (7DS). The aims of this study were to describe the clinical syndrome in detail based on an institutional case series and literature review. Methods: A retrospective review of adult patients that underwent deceased donor liver transplantation at our institution between January 2010 and 2020 was performed to identify patients that developed 7DS. Relevant clinical variables were obtained from medical records. Existing cases in the literature were identified by a systematic literature search according to PRISMA guidelines. Pooled analysis was used to describe the incidence, retransplantation, and mortality rate. Histological findings from institutional and published literature cases were collected and appraised. Results: Six of 1907 liver transplantations at our institution (0.3%) developed 7DS. Seven case series, describing 42 patients with 7DS, and two single case reports were identified from literature review. Pooled incidence of 7DS was low (2.1%, 95%CI: 0.7%-3.9%) and associated with high mortality (74.8%, 95%CI: 49.2%-94.6%). Retransplantation was performed in 23/42 (55%) patients and 4/23 (17%) survived. Review of histology showed frequent intrahepatic thrombi and arteritis. Rejection, with features of potential antibody mediated rejection, often preceded or accompanied progressive zonal coagulative necrosis and haemorrhage. Conclusions: 7DS is a rare clinical syndrome after liver transplantation and associated with high mortality. Antibody-mediated rejection, as suggested in early reports, is likely to be involved in the pathogenesis. Early recognition would allow rapid clinical diagnostics and expedited decisions, such as treatment of AMR if diagnosed or early retransplantation.